2020
DOI: 10.1055/a-1224-6822
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-band imaging versus Lugol chromoendoscopy for esophageal squamous cell cancer screening in normal endoscopic practice: randomized controlled trial

Abstract: Objective: Narrow-Band Imaging (NBI) is as sensitive as Lugol chromoendoscopy to detect oesophageal squamous cell carcinoma (SCC) but its specificity, which appears higher than than that of Lugol chromoendoscopy in expert centres, remains to be established in current practice. This study aimed to prove the superiority of NBI specificity over Lugol chromoendoscopy in the detection of oesophageal SCC and high-grade dysplasia (HGD) in current practice (including tertiary care centres, local hospitals, and private… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…The sensitivity, specificity, and positive and negative likelihood values of NBI were 100%, 79.9%, 37.5%, and 100%, respectively. These values for Lugol chromoendoscopy were 100%, 66.0%, 21.2%, and 100%, respectively [18]. The NBI feature was not used as a predictor in our study because there is no standard NBI classification; while NBI is helpful in finding existing dysplastic lesions, it cannot predict the risk of metachronous ESCN.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…The sensitivity, specificity, and positive and negative likelihood values of NBI were 100%, 79.9%, 37.5%, and 100%, respectively. These values for Lugol chromoendoscopy were 100%, 66.0%, 21.2%, and 100%, respectively [18]. The NBI feature was not used as a predictor in our study because there is no standard NBI classification; while NBI is helpful in finding existing dysplastic lesions, it cannot predict the risk of metachronous ESCN.…”
Section: Discussionmentioning
confidence: 78%
“…IEE with NBI and Lugol chromoendoscopy is a widely used screening tool [17,18]. Based on the systemic review and meta-analysis study, Lugol chromoendoscopy and NBI had high detection rates of ESCN from aerodigestive tract patients (the area under the summary receiver operating characteristic curve(sROC), Lugol: 0.96 vs. NBI: 0.96).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials are another method by which the AI system's performance could be evaluated. However, ESCC is not a common cancer, and the prevalence of ESCC in prospective studies has been 1.9% (2/105 cases) 19 to 10.8% (36/334 cases) 20 even in high‐risk populations. Evaluating the performance of the AI system with a large number of ESCCs would require a long investigative period and be expensive, in contrast to the current study, in which we directly compared the endoscopists' diagnostic performance with that of the AI system.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that NBI was more specific than LCE in the current gastroenterology practice for the detection of early ESCC as previously demonstrated in expert centers. 54 The education program for non-expert or less experienced endoscopists may prove useful in improving the diagnostic accuracy of NBI during surveillance or screening endoscopy. Recently, NBI with a "dual-focus" mode (DF-NBI) was developed.…”
Section: Nbi With or Without Magnification A Esophageal Squamous Cell Dysplasia And Carcinomamentioning
confidence: 99%